2000
DOI: 10.1007/bf03162115
|View full text |Cite
|
Sign up to set email alerts
|

ESR, ENDOR, and ESEEM investigations on UV-irradiated 2,4,6-tri-tert-butyl phenol crystals

Abstract: Electron spin resonance (ESR), electron nuclear double resonance (ENDOR), and electron spin echo envelope modulation (ESEEM) measurements were carried out for UV-irradiated 2,4,6-tri-tert-butyl phenol in the polycrystalline state. The radical produced in the crystal was detected by ESR and identified to be the corresponding phenoxyl radical, which is well characterized in the chemical oxidations in solutions. ENDOR and ESEEM spectra were unambiguously analyzed in terms of the hyperfine coupling constants deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The EPR spectrum (Figure 1A) of the radical in irradiated 2,4,6-tri-tert-butyl-phenol (2,4,6-t-Bu-phenol) is a single line with unresolved hyperfine coupling to the ring protons and to the tert-butyl methyl protons. 40 The EPR spectrum of the radical in irradiated glycylglycine (Figure 1B) exhibits resolved coupling to a single proton with A H ∼ 18 G. 41,42 The room-temperature EPR spectrum of the dominant stable radical in irradiated L-alanine (Figure 1C) exhibits approximately equal coupling (∼25 G) to a unique proton and to the protons of a methyl group. For the radical in irradiated 4-methyl-2,6-di-tert-butyl-phenol (4-Me-2,6-t-Bu-phenol), the coupling to the three equivalent protons of the 4-methyl group in the fast methyl-rotation regime is about 11 G. 17,18,43,44 Comparison of the relaxation processes for the radical in L-alanine and for the 4-Me-2,6-t-Bu-phenoxy radical with those for the 2,4,6-t-Bu-phenoxy radical shows the differences between the effects on T 1e of methyl protons that give resolved hyperfine splittings and more weakly coupled methyl protons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPR spectrum (Figure 1A) of the radical in irradiated 2,4,6-tri-tert-butyl-phenol (2,4,6-t-Bu-phenol) is a single line with unresolved hyperfine coupling to the ring protons and to the tert-butyl methyl protons. 40 The EPR spectrum of the radical in irradiated glycylglycine (Figure 1B) exhibits resolved coupling to a single proton with A H ∼ 18 G. 41,42 The room-temperature EPR spectrum of the dominant stable radical in irradiated L-alanine (Figure 1C) exhibits approximately equal coupling (∼25 G) to a unique proton and to the protons of a methyl group. For the radical in irradiated 4-methyl-2,6-di-tert-butyl-phenol (4-Me-2,6-t-Bu-phenol), the coupling to the three equivalent protons of the 4-methyl group in the fast methyl-rotation regime is about 11 G. 17,18,43,44 Comparison of the relaxation processes for the radical in L-alanine and for the 4-Me-2,6-t-Bu-phenoxy radical with those for the 2,4,6-t-Bu-phenoxy radical shows the differences between the effects on T 1e of methyl protons that give resolved hyperfine splittings and more weakly coupled methyl protons.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the effectiveness of methods for measuring T 1e in samples with various spectral diffusion processes, radicals with different proton hyperfine coupling patterns were selected (Figure ). The EPR spectrum (Figure A) of the radical in irradiated 2,4,6-tri- tert -butyl-phenol (2,4,6- t -Bu-phenol) is a single line with unresolved hyperfine coupling to the ring protons and to the tert -butyl methyl protons . The EPR spectrum of the radical in irradiated glycylglycine (Figure B) exhibits resolved coupling to a single proton with A H ∼ 18 G. , The room-temperature EPR spectrum of the dominant stable radical in irradiated l -alanine (Figure C) exhibits approximately equal coupling (∼25 G) to a unique proton and to the protons of a methyl group.…”
Section: Introductionmentioning
confidence: 99%
“…ESR and ENDOR studies have revealed that the radical produced by UV irradiation is TTBP and is dispersed homogeneously in a diamagnetic matrix of the corresponding phenol [5]. The EPR spectrum of DTBMP is also anisotropic due to the g-values but is essentially composed of four lines with an intensity ratio of 1:3:3:1, which can be assigned to "three methyl pr 0-tons at the para-position.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the difficulty of radical production, the irradiation time for DTBMP was doubled. Details of the sample preparation were also desc¡ in a previous paper [5]. The radical concentrations determined from CW-EPR spin counting were 5.0" l017 and 6.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation